Educating a Tolerant Society: Experience in the Kwangenrejo Kalitidu Bojonegoro Religious Moderation Village - Yaqin, Ahmad Ainul; Yenuri, Ali Ahmad (Program Pascasarjana Pendidikan Islam Universitas Islam Darul Ulum Lamongan, 2024)
Kwangenrejo is a village where there are two religions, namely Christianity and Islam. They maintain mutual tolerance. This research examines the implementation of their way of educating people to have a tolerant attitude that is passed down to generations. This research use desciptive qualitative approach. Data analysis uses data reduction, data presentation, and drawing conclusions. Data validity uses triangulation with sources, techniques and time. The results of the research show that the formation of a convert's personality does not occur spontaneously or directly, it requires a process and also includes several elements of the spiritual competence of a good educator who is wise in carrying out his duties, manifested by the educator's behavior being in accordance with religious norms, not easily angered. angry with converts who sometimes ask strange questions and also sometimes make mistakes, but on the contrary, educators will provide advice and direction